RANCANG BANGUN PROTOTYPE SISTEM ABSENSI IOT BERBASIS ESP32-CAM DAN FACE RECOGNITION PADA PROGRAM MAKAN BERGIZI SEKOLAH - Risqi Novriandi (Universitas Lampung, 2026)
IoT-based automated attendance systems are highly sought after because they can improve the efficiency of the attendance process in educational institutions and offices. This research develops an attendance system using an ESP microcontroller integrated with a camera, identifying faces using face-api.js, and storing data to a database in real time. Testing was conducted with a number of participants and was able to improve the accuracy and efficiency of attendance. The results of this research provide a digital attendance solution that is easy to implement with a good level of security.